2013
DOI: 10.3390/cancers5010234
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Immune Response in Merkel Cell Carcinoma

Abstract: Merkel cell carcinoma (MCC) is an aggressive neuroendocrine skin cancer. The Merkel cell polyomavirus (MCPyV) is implicated in its pathogenesis. Immune mechanisms are also implicated. Patients who are immunosuppressed have an increased risk. There is evidence that high intratumoral T-cell counts and immune transcripts are associated with favorable survival. Spontaneous regressions implicate immune effector mechanisms. Immunogenicity is also supported by observation of autoimmune paraneoplastic syndromes. Case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 114 publications
1
32
1
Order By: Relevance
“…The role of MCPyV in MCC development, along with the fact that immune-suppressed individuals are more likely to develop this cancer, indicate that the host immune response plays a key role in MCC tumorigenesis [54]. Additional evidence such as complete spontaneous tumor regression and tumor reactive T cells all support the role of the immune system in preventing and controlling MCC [55]. Furthermore, MCC patients with robust immune response generally have better prognoses, and high intratumoral CD8+ and CD4+ lymphocyte infiltration predicts better survival [5658].…”
Section: Mcpyv Infection Host Immune Responses and MCCmentioning
confidence: 99%
“…The role of MCPyV in MCC development, along with the fact that immune-suppressed individuals are more likely to develop this cancer, indicate that the host immune response plays a key role in MCC tumorigenesis [54]. Additional evidence such as complete spontaneous tumor regression and tumor reactive T cells all support the role of the immune system in preventing and controlling MCC [55]. Furthermore, MCC patients with robust immune response generally have better prognoses, and high intratumoral CD8+ and CD4+ lymphocyte infiltration predicts better survival [5658].…”
Section: Mcpyv Infection Host Immune Responses and MCCmentioning
confidence: 99%
“…Individuals with Merkel cell polyoma virus positivity are thought to have a more favorable outcome, possibly due to the immune response triggered by the virus. [10] Our patient showed complete regression of lesions within 1 month of biopsy. The presence of Merkel cell polyoma virus was not assessed in our case.…”
Section: Discussion Discussionmentioning
confidence: 85%
“…On the other hand, it is suggested that some form of immune modulation may result in (complete) tumour regression. This theory is supported by the various histopathological observations in patients with complete spontaneous regression of MCC, which show signs of chronic inflammation with humoral and cellular immune responses leading to replacement of the original tumour cells 1 16. Since biopsy preceded the complete regression in all of the written case reports, it is plausible to conclude that this probably was the triggering mechanism.…”
Section: Discussionmentioning
confidence: 88%